2013
DOI: 10.1007/s12010-013-0225-z
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Structure and In Vitro Antitumor Activity of Rhamnolipids from Pseudomonas aeruginosa BN10

Abstract: A newly isolated indigenous strain BN10 identified as Pseudomonas aeruginosa was found to produce glycolipid (i.e., rhamnolipid-type) biosurfactants. Two representative rhamnolipidic fractions, RL-1 and RL-2, were separated on silica gel columns and their chemical structure was elucidated by a combination of nuclear magnetic resonance and mass spectroscopy. Subsequently, their cytotoxic effect on cancer cell lines HL-60, BV-173, SKW-3, and JMSU-1 was investigated. RL-1 was superior in terms of potency, causing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
34
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(38 citation statements)
references
References 27 publications
0
34
0
Order By: Relevance
“…Rhamnose‐lipids, or rhamnolipids, are the most intensively studied glycolipid biosurfactant. Due to the advantages in physicochemical and biological properties, rhamnolipids are widely used in many fields, such as environmental remediation, oil recovery, food production, cosmetics, and pharmaceutics (Amani, ; Amani, Müller, Syldatk, & Hausmann, ; Bachmann, Johnson, & Edyvean, ; Bharali, Saikia, Ray, & Konwar, 2013; Christova et al, ; Dashtbozorg, Miao, & Ju, ; Pornsunthorntawee, Chavadej, & Rujiravanit, ; Vu, Tawfiq, & Chen, ; Yan, Xu, Chen, & Zheng, ). To our knowledge, several good review articles focused on specific topics of rhamnolipids in therapeutic, biomedical, pharmaceutical, and industrial applications have been published (Banat et al, ; Gudiña, Rangarajan, Sen, & Rodrigues, ; Inès & Dhouha, ; Nitschke, Costa, & Contiero, ).…”
Section: Introductionmentioning
confidence: 99%
“…Rhamnose‐lipids, or rhamnolipids, are the most intensively studied glycolipid biosurfactant. Due to the advantages in physicochemical and biological properties, rhamnolipids are widely used in many fields, such as environmental remediation, oil recovery, food production, cosmetics, and pharmaceutics (Amani, ; Amani, Müller, Syldatk, & Hausmann, ; Bachmann, Johnson, & Edyvean, ; Bharali, Saikia, Ray, & Konwar, 2013; Christova et al, ; Dashtbozorg, Miao, & Ju, ; Pornsunthorntawee, Chavadej, & Rujiravanit, ; Vu, Tawfiq, & Chen, ; Yan, Xu, Chen, & Zheng, ). To our knowledge, several good review articles focused on specific topics of rhamnolipids in therapeutic, biomedical, pharmaceutical, and industrial applications have been published (Banat et al, ; Gudiña, Rangarajan, Sen, & Rodrigues, ; Inès & Dhouha, ; Nitschke, Costa, & Contiero, ).…”
Section: Introductionmentioning
confidence: 99%
“…Glycolipids offer numerous advantages in terms of biodegradability, lower toxicity, surface tension reduction and emulsification activity, stability at varying temperature/pH, which make them unique for several broad range industrial applications unlike their chemically synthesized counterparts [4][5][6]. Among various glycolipids, rhamnolipids (RL), due to its versatile nature, are well known for their potent cytotoxic effects against Hep G2 cells, HeLa cells and MCF-7 cell lines [7,8]. The unique ability to reduce surface tension (ST) help glycolipids to easily attach to the membrane of the cell and/or dissipated to the surrounding environments [9].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Isoda and Nakahara 134 proposed that MEL directly down-regulates the tyrosine kinase activities of human myelogenous leukemia cell line K562 to inhibit the cell proliferation and to induce the granulocytic differentiation.Moreover, P. aeruginosa derived rhamnolipid exhibited efficient cytotoxic potencies against different human tumor cell lines such as HeLa, HepG2, A549, and MDA MB 231 135. A P. aeruginosa BN10 strain produced two rhamnolipid-type biosurfactants showing cytotoxic effect on cancer cell lines HL-60, BV-173, SKW-3, and JMSU-1 suggesting their potential application in biomedicine as a new and promising therapeutic agent 28. In fact, rhamnolipid-1 was superior in terms of potency, causing 50 % inhibition of cellular viability at lower concentrations, as compared to rhamnolipid-2; the results from fluorescent staining analysis demonstrated that rhamnolipid-1 inhibited proliferation of BV-173 pre-B human leukemia cells by induction of apoptotic cell death 28.…”
mentioning
confidence: 99%
“…A P. aeruginosa BN10 strain produced two rhamnolipid-type biosurfactants showing cytotoxic effect on cancer cell lines HL-60, BV-173, SKW-3, and JMSU-1 suggesting their potential application in biomedicine as a new and promising therapeutic agent 28. In fact, rhamnolipid-1 was superior in terms of potency, causing 50 % inhibition of cellular viability at lower concentrations, as compared to rhamnolipid-2; the results from fluorescent staining analysis demonstrated that rhamnolipid-1 inhibited proliferation of BV-173 pre-B human leukemia cells by induction of apoptotic cell death 28. …”
mentioning
confidence: 99%
See 1 more Smart Citation